2015
DOI: 10.1371/journal.pone.0124446
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Foot Complications and Their Risk Factors from a Large Retrospective Cohort Study

Abstract: BackgroundFoot complications are considered to be a serious consequence of diabetes mellitus, posing a major medical and economical threat. Identifying the extent of this problem and its risk factors will enable health providers to set up better prevention programs. Saudi National Diabetes Registry (SNDR), being a large database source, would be the best tool to evaluate this problem.MethodsThis is a cross-sectional study of a cohort of 62,681 patients aged ≥25 years from SNDR database, selected for studying f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
288
11
24

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(405 citation statements)
references
References 54 publications
(68 reference statements)
42
288
11
24
Order By: Relevance
“…Conversely, the number of treatments and the score of practice of foot selfcare were protective factors. In agreement with this, a study in Saudi Arabia revealed that the foot complications increased with the duration of the disease (Al- Rubeaan et al, 2015). A similar finding was also reported from studies in Turkey (Saltoglu et al, 2015) and Poland (Nehring, 2015) …”
Section: Discussionsupporting
confidence: 77%
“…Conversely, the number of treatments and the score of practice of foot selfcare were protective factors. In agreement with this, a study in Saudi Arabia revealed that the foot complications increased with the duration of the disease (Al- Rubeaan et al, 2015). A similar finding was also reported from studies in Turkey (Saltoglu et al, 2015) and Poland (Nehring, 2015) …”
Section: Discussionsupporting
confidence: 77%
“…A study in Southeastern Nigeria found a male to female ratio of 1.9:1. Another study done in Saudi Arabia, found men to represent 68.57% of the subjects [14,15]. Most of the study subjects were middle-aged.…”
Section: Discussionmentioning
confidence: 99%
“…8 Of these, modifiable factors including BMI and HbA1c have gained special attention of researchers and have been extensively studied in relation with diabetic foot ulcers, gangrene, and limb amputation. 9 BMI is closely linked with obesity and type 2 diabetes mellitus. In fact, obesity is accounted for as one of the higher risk factors for diabetes.…”
Section: Discussionmentioning
confidence: 99%